The Role of Conscientiousness Personality in Predicting Marital Satisfaction in Married Individuals - Lia Aulia Fachrial; Cahyanti, Indah; Fauziah, Alia Rizki (Jurnal Kesehatan dan Kedokteran, 2025)
This study aims to determine the influence of the personality trait of conscientiousness on marital satisfaction in married adults. Marital satisfaction is a subjective feeling felt by a married couple regarding various aspects of married life such as happiness, communication, and commitment, while conscientiousness describes the characteristics of individuals who are diligent, disciplined, responsible, and goal-oriented. This study used a quantitative approach with a simple linear regression method. The sample was obtained through a purposive sampling technique with the criteria of respondents being at least 21 years old, having been married for at least one year, and still having a spouse. The instruments used were the Enrich Marital Satisfaction Scale  and Big Five Personality Inventory. The results of the analysis showed a significant influence between conscientiousness and marital satisfaction with a significance value of p = 0.010 (p < 0.05) and an R² value of 0.067, which means that conscientiousness provides an effective contribution of 6.7% to marital satisfaction, while 93.3% is influenced by other factors outside the study. These findings indicate that individuals with high levels of conscientiousness tend to have more satisfying marital relationships because they are able to manage conflict, maintain commitment, and create emotional stability in the relationship. The results of this study are expected to be the basis for developing psychological interventions and marital counseling to improve the quality of marital relationships.